Women's views on communication with health care providers about pre-exposure prophylaxis (PrEP) for HIV prevention. Issue 5 (13th April 2022) - Jackson, Gabriella Y.; Darlington, Caroline K.; Van Tieu, Hong; Brawner, Bridgette M.; Flores, Dalmacio D.; Bannon, Jacqueline A.; Davis, Annet; Frye, Victoria; Chittamuru, Deepti; Gugerty, Paige; Koblin, Beryl A.; Teitelman, Anne M.
Abstract: Since the beginning of the HIV epidemic in the USA, effective interventions to reduce HIV risk among cisgender women have been lacking. Although oral HIV pre-exposure prophylaxis (PrEP) is effective in pharmacologically preventing HIV infection, there is a gap between the recommended use of PrEP and PrEP uptake among eligible women. This study aimed to identify the role of patient-provider communication in PrEP decision-making among women considering PrEP. Semi-structured in-depth interviews were conducted with 41 PrEP-eligible women in Philadelphia and New York City. A thematic analysis of the responses was conducted, and a conceptual model developed and confirmed as analysis continued. Of the women interviewed, 53.6% were African American and 29.3% were Latina. Women noted that having a trusting relationship with their health care provider, receiving a tailored recommendation for PrEP based upon their specific needs and using their health care provider as support were crucial facilitators of PrEP decision-making. Lack of provider knowledge about PrEP, perceived health care provider stigma about their drug use and sexual activity, and lack of care continuity were all identified as barriers to effective communication. Study findings can inform future interventions to enhance patient-provider communication about PrEP and increase PrEP uptake among women.